Regioselective 1,2-Alkoxy and Hydroxy Iodination of Alkenes by 1,4-Dibenzyl-1,4-Diazabicyclo[2.2.2]Octane Dichloroiodate - Mohammad Alikarami (Science Faculty of Chiang Mai University, 2019)
The reaction of 1,4-dibenzyl-1,4-diabicyclo [2.2.2] octane dichloroiodate (DBDDCI) with alkenes in the presence of oxygenated nucleophilic solvents (alcohols or H2O/CH3CN (1:1)) in mild and under catalyst free condition at room temperature led to the corresponding β-iodoethers and iodohydrines in good to excellent yield.